“The Bold Men Will Have a Long Life”: The Masculinist Discourse in Contemporary Ukrainian Fiction - Kamińska-Maciąg, Sylwia (Literatura Ludowa. Journal of Folklore and Popular Culture, 2018)
Reviw of book: Mateusz Świetlicki, Kiedy chłopcy zostają mężczyznami? Męskość jako projekt w prozie Serhija Żadana, Wydawnictwo Uniwersytetu Wrocławskiego, Wrocław 2016, ss. 180.